Pipelle Endometrial Sampling and Morphological Findings in Women with Abnormal Uterine Bleeding - Sahar Salahuddin Amir, Aman-ur-Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The abnormal uterine bleeding has many causes and consequences in women. The exact causes are described by histology of sample through D&C. Pipple biopsy samples is considered one of the least invasive, OPD setting technique, comparable to D&C. Objective: To see the adequacy of Pipelle endometrial sampling and morphological findings among women with abnormal uterine bleeding. Study Design: Cross-sectional descriptive study Place and Duration of Study: Department of Gynaecology & Histopathology, Shaikh Zayed Hospital Lahore from 1st May to 31st December 2021. Methodology: Two hundred and thirty seven adult women with AUB recommended for D&C were included. Those with endometrial thickness less than 4mm, having fibroids, with pelvic inflammatory disease, or clotting factor disorders were excluded. Pipelle endometrial sample was taken in Gyne OPD and were examined at Histopathology Department. Results: 80.0% were sampled adequately through Pipelle. Secondary endometrium was most common in 39.9% followed by proliferative endometrium in 36.2% and chronic endometritis 12.2%. There were 6 cases with carcinoma, 4 (2.1%) with adenocarcinoma and 2(1.1%) squamous cell carcinoma. Conclusion: Pipelle Endometrial sampling can be considered an effective methods for endometrial sampling. Keywords: Abnormal uterine bleeding, Pipelle endometrial biopsy, Sample adequacy, Endometrial pathology